A Green and Low-Cost Approach to Synthesize Bamboo Charcoal@Si@C Composites as Anode for High-Performance Li-Ion Batteries. Issue 15 (1st November 2019) - Gu, Zhiqiang; Li, Wenli; Liu, Chan; Chen, Yuxi; Li, Run; He, Yuede; Xia, Xiaohong; Liu, Hongbo
Abstract : Here, A novel biomass carbon@Si composites (bamboo charcoal@Si@C) is reported via a green and low-cost way. Silicon nanoparticles are encapsulated into pores of bamboo charcoal since the pore's sizes of the bamboo charcoal (∼1–2 μm) are ten times larger than that of the silicon nanoparticles (∼80 nm). There is also sufficient space in charcoal to tolerate the volume alteration of silicon during the charge and discharge process. Due to high structural stability and excellent electronic conductivity of the bamboo charcoal, the obtained bamboo charcoal@Si@C composite anode exhibits remarkable synergistic effect in electrochemical performance, which delivers a cyclic or reversible capacity of 515 mAh g −1 after 500 discharge/charge cycles at a current density of 100 mA g −1 . The reversible capacity can reach 380 mAh g −1 even at a high current density of 2000 mA g −1, which is much higher than those of the bare Si and the bamboo charcoal anodes. The bamboo charcoal@Si@C composite is a promising anode candidate for high-performance lithium-ion batteries.